Recombinant Endostatin as a Potential Radiosensitizer in the Treatment of Non-Small Cell Lung Cancer - Charnay Cunningham; Julie Bolcaen; Alessandra Bisio; Amanda Genis; Hans Strijdom; Charlot Vandevoorde (MDPI AG, 2023)
Non-small cell lung cancer (NSCLC) is the most prevalent type of lung cancer, which is the leading cause of cancer-related deaths worldwide. Over the past decades, tumour angiogenesis has been intensely studied in the treatment of NSCLC due to its fundamental role in cancer progression. Several anti-angiogenic drugs, such as recombinant endostatin (RE), have been evaluated in several preclinical and clinical trials, with mixed and often disappointing results. However, there is currently an emerging interest in RE due to its ability to create a vascular normalization window, which could further improve treatment efficacy of the standard NSCLC treatment. This review provides an overview of preclinical and clinical studies that combined RE and radiotherapy for NSCLC treatment. Furthermore, it highlights the ongoing challenges that have to be overcome in order to maximize the benefit; as well as the potential advantage of combinations with particle therapy and immunotherapy, which are rapidly gaining momentum in the treatment landscape of NSCLC. Different angiogenic and immunosuppressive effects are observed between particle therapy and conventional X-ray radiotherapy. The combination of RE, particle therapy and immunotherapy presents a promising future therapeutic triad for NSCLC.